2013
DOI: 10.1038/emboj.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Homeobox proteins and Polycomb repressive complexes in p16INK4a regulation

Abstract: The INK4/ARF locus regulates senescence and is frequently altered in cancer. In normal cells, the INK4/ARF locus is found silenced by Polycomb repressive complexes (PRCs). Which are the mechanisms responsible for the recruitment of PRCs to INK4/ARF and their other target genes remains unclear. In a genetic screen for transcription factors regulating senescence, we identified the homeodomain-containing protein HLX1 (H2.0-like homeobox 1). Expression of HLX1 extends cellular lifespan and blunts oncogene-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
(66 reference statements)
1
38
0
Order By: Relevance
“…INK4a -dependent cell cycle arrest (Martin et al 2013). Our findings identify Hhex as a crucial homeobox protein that similarly enables PRC2 function at the Cdkn2a locus to maintain the self-renewal capacity of MLL-ENL-induced AML.…”
Section: Arfmentioning
confidence: 81%
See 1 more Smart Citation
“…INK4a -dependent cell cycle arrest (Martin et al 2013). Our findings identify Hhex as a crucial homeobox protein that similarly enables PRC2 function at the Cdkn2a locus to maintain the self-renewal capacity of MLL-ENL-induced AML.…”
Section: Arfmentioning
confidence: 81%
“…INK4a and p19 ARF expression via regulation of PRC2 function Previous studies have indicated an important role for homeobox transcription factors, including Hoxa9 and Hlx1, in the recruitment of PRC2 to the Cdkn2a/b locus to facilitate transcriptional repression and the maintenenace of self-renewal potential (Martin et al 2013;Collins et al 2014). We therefore tested whether Hhex mediates repression of this locus in AML cells via PRC2-mediated epigenetic silencing using antibodies directed against the PRC2-encoded repressive mark H3K27me3 as well as the activating mark H3K4me3 for chromatin B H E T K O IGF2R NAAA SLFN5 USP18 DDX58 AMOT AGAP1 SBF2 PARP14 CDKN2A RASSF10 ADAMDEC1 TRIM34A PLXNC1 DDX60 RTP4 XAF1 IRGM2 ZBP1 BMP8A SAMD4 HOXA11 ISG15 TRIM30D HOXA11OS TGM3 CHPF TMEM198 TESC immunoprecipitation (ChIP) sequencing.…”
Section: Hhex Represses P16mentioning
confidence: 99%
“…Hoxa9 represses Ink4a expression to overcome oncogene-induced senescence during transformation by AML1-ETO in Bmi1−/− cells, as well as in Hoxa9/Meis1 transformed cells (10, 83). This repression may be the result of direct recruitment of EZH2 by Hoxa9, however recent work suggests that EZH2 may also regulate p16 in HOXA9-independent fashion in MLL -rearranged leukemias (84, 85). …”
Section: Transcriptional Regulation and Transformation By H/mmentioning
confidence: 99%
“…Recently, H2.0-like homeobox 1 (HLX1), a homeobox (HOX) protein, was shown by Martin et al to facilitate PRC2 recruitment to the p16 INK4a promoter (Fig. 2A and (52)). While the mechanism has yet to be defined, six other homeobox-containing proteins (HOXA9, DLX3, HOXB13, HOXC13, HOXD3 and HOXD8) were similarly reported to participate in p16 INK4a silencing (52).…”
Section: Transcriptional Translational and Epigenetic Regulation Of mentioning
confidence: 99%